2013
DOI: 10.5513/jcea01/14.3.1328
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biologically Active Substances in Bilberry (Vaccinium Myrtillus L.) in Selected Natural Localities of Slovak Republic

Abstract: The bioactive substances such as total polyphenols, anthocyanins, quercetin, chlorogen acid, pterostilbene and antioxidant activity in samples of bilberry (Vaccinium myrtillus L.) from different natural localities of the Slovak Republic -Oščadnica and Liesek (northwestern Slovakia), Poprad, Kežmarok, Stará Ľubovňa (northeastern Slovakia) and one sample of blueberry (Vaccinium corymbosum L.) from local supermarket was determined. The total of polyphenols ranged from 33772.5 ± 737.99 mg*kg -1 dw (Kežmarok) to 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Kalt et al (2000) found a positive correlation relationship between the antioxidant capacity and concentration of total polyphenols. This finding agrees with data previously reported by other authors (Kačániová et al, 2008;Habánová et al, 2013). Beliveau and Gingras (2005) reported that the antioxidant properties are a common feature of many plants and actually impede the action of free radicals, in particular in the oxidation of the blood vessel walls, causing a number of vascular diseases.…”
Section: Resultssupporting
confidence: 92%
“…Kalt et al (2000) found a positive correlation relationship between the antioxidant capacity and concentration of total polyphenols. This finding agrees with data previously reported by other authors (Kačániová et al, 2008;Habánová et al, 2013). Beliveau and Gingras (2005) reported that the antioxidant properties are a common feature of many plants and actually impede the action of free radicals, in particular in the oxidation of the blood vessel walls, causing a number of vascular diseases.…”
Section: Resultssupporting
confidence: 92%
“…There has been a previous study of bilberries in Slovakia [17] but the authors have made no attempt to evaluate the environmental influence on the amounts of the secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of blueberry (Vaccinium myrtillus) and sea buckthorn (Hippophae rhamnoides) extract for children with type 1 diabetes for 2 months elicited a reduction in HBA1c levels and an increase in SOD and glutathione peroxidase levels [37]. Since pterostilbene has been isolated from Vaccinium myrtillus [38], this effect may be ascribable to the presence of pterostilbene alongside other bioactive compounds in the excerpt.…”
Section: Clinical Studies On Rsv On Diabeticmentioning
confidence: 99%